The wedding banquet [videorecording (DVD)] - Schamus, James, 1959-; Ahn, Andrew; Yang, Bowen; Gladstone, Lily; Tran, Kelly Marie (Decal, 2025)
From Director Andrew Ahn comes a joyful comedy of errors about a chosen family navigating the disasters and delights of family expectations, queerness, and cultural identity. Angela and her partner Lee have been unlucky with their IVF treatments but can't afford to pay for another round. Meanwhile their friend Min, the closeted scion of a multinational corporate empire, has plenty of family money but a soon-to-expire student visa. When his commitment-phobic boyfriend Chris rejects his proposal, Min makes the offer to Angela instead: a green card marriage in exchange for funding Lee's IVF. But their plans to quietly elope are upended when Min₂s skeptical grandmother flies in from Korea unannounced, insisting on an all-out wedding extravaganza. With a pitch-perfect cast of multigenerational talent, this fresh reimagining of Ang Lee's beloved, Award-winning rom-com teems with humor and heart in a poignant reminder that being part of a family means learning to both accept and forgive.